El fenómeno de la xenofobia en Costa Rica desde una perspectiva histórica - J. Solís, Pedro (Universidad de Costa Rica, 2010)
It is presented an analysis of xenophobia in Costa Rica from a historical point of view. This approach makes possible to comprehend the phenomenon in question in relation to some factors that determine its apparition, among them we consider factors of economical, political and cultural type that define the sociohistorical context in which xenophobia appears.